GC-MS analysis of the bioactive compounds of Acmella calva (DC) R. K. Jansen influenced by AMF - S. C. Khilare and S. A. Patole (South Eastern European Journal of Public Health, 2025)
Medicinal plants are widely recognized as a storage pool of numerous effective drugs, which have pharmaceutical efficacy in diverse diseases based on the presence and abundance of secondary metabolites. Acmella calva (DC) R. K. Jansen is a medicinal herb traditionally used as a toothache plant to treat stomatitis, mouth ulcers, and different gum-related problems. The present study aimed to investigate the effect of three distinct species of Arbuscular mycorrhizal fungi (AMF) individually (Funneliformis mosseae, Glomus macrocarpum, and Gigaspora margarita) and in combination (F. mosseae + Gi. margarita) on the phytochemical composition in A. calva. The findings showed an increased concentration of terpenoids, alkaloids, hydrocarbons and lipids in ethanolic extracts of A. calva inoculated with AMF. The GC- MS screening of ethanolic extract of A. calva revealed the presence of terpenoids, alkanes, hydrocarbons and lipids as major active compounds with the varying % area found in combined AMF (F. mosseae + Gi. margarita) treatment, it evidenced by their highest % peak area. Furthermore, the plants inoculated with F. mosseae showed nine different bioactive compounds viz. sesquiterpenoids, hydrocarbon, terpenoid, alkane, ester and terpenoids groups. Among them, Phytol reported with highest peak area (40.69%), followed by 3,7,11,15-Tetramethyl-2-hexadecen-1-ol (4.55%), and Nonacosane (4.36%). A. calva inoculated with G. macrocarpum showed the highest % peak area of Phytol (21.62%), followed by Neophytadiene (12.93%), and 3,7,11,15-Tetramethyl-2-hexadecen-1-ol (7.80%). Inoculation of Gi. margarita showed five different compounds with the highest % peak area of Stigmasterol (45.34%), followed by Neophytadiene (22.77%), and Phytol (21.62 %) in comparison with control. From GC-MS analysis of A. calva, it was concluded that Mix AMF (F. mosseae + Gi. margarita) inoculation enhanced the production of secondary metabolites in A. calva which may be due to improved mineral nutrition and transfer in the AMF host interphase. The present study exhibited the inoculation of AMF leads to an increase in medicinal potential of A. calva.